Methodology For Developing Students' Software Creativity On The Basis Of Teaching The Subject Of "Electronic Pedagogy" (Eurasian Journal of Research, Development and Innovation, 2026)
This in the article "Electronic "pedagogy" subject to teach in the process students software creativity develop methodology illuminated. Modern information in society future of educators software supply create and adaptation competencies has to be important importance profession Research within students software creativity to develop aimed at methodical system working issued be, he constructivist approach, problematic education and project based on to teach to the methods relies on. The methodology efficiency pedagogical experiment through checked results students software creativity indicators (fluency, flexibility, originality) and working exit) significant at the level increased The study showed that results supreme education " Electronic" in institutions "pedagogy " subject to teach practice to improve service does .